Bioengineering of cloneable inorganic nanoparticles - Hendricks, Alexander Ryo, author; Ackerson, Christopher J., advisor; Chung, Jean, committee member; McNally, Andy, committee member; Cohen, Bob, committee member (Colorado State University. Libraries, 2023)
When a defined protein/peptide (or combinations thereof) control and define the synthesis of an inorganic nanoparticle, the result is a cloneable NanoParticle (cNP). This is because the protein sequence/structure/function is encoded in DNA, and therefore the physicochemical properties of the nanoparticle are also encoded in DNA. Thus the cloneable nanoparticle paradigm can be considered as an extension of the central dogma of molecular biology (e.g. DNA -> mRNA -> Protein -> cNP); modifications to the DNA encoding a cNP can modify the resulting properties of the cNP. The DNA encoding a cNP can be recombinantly transferred into any organism. Ideally, this enables recombinant production of cNPs with the same defined physiochemical properties. Such cNPs are of primary interest for applications in biological imaging as clonable contrast agents. The advancement of cNPs for broader and more rigorous applications in imaging (and elsewhere) requires further development through multidisciplinary approaches. Described in This Thesis is a bioengineering approach to improve the cNP platform through development of the enzymes responsible for nanoparticle formation.In the first chapter, background and significance is given to provide rationale behind the cNP platform. Among all the modalities of biological imaging, there is no 'one-size-fits-all' solution. Biological fluorescence microscopy (FM) and electron microscopy (EM) are the preferred methods of choice when imaging at cellular levels. Although the relatively recent advent of fluorescent proteins and super-resolution microscopy have ushered major scientific breakthroughs, FM is resolution-limited: only the cellular components which are labeled by fluorophores can be resolved – everything else in a cell (~99% of components) is imaged with low resolution owing to the diffraction limit of light. Biological EM comparatively can image widefield cells at atomic-level resolution yet lacks an analogous toolset to fluorescent proteins. cNPs are proposed as a multimodal, uniform, and precise means of clonable contrast for biological EM (and other modalities) analogous to fluorescent proteins. In the second chapter, a tellurium reductase is isolated and characterized from screened environmental bacterial cultures collected throughout the Colorado Mineral Belt. A strain of Rhodococcus erythropolis PR4 was found to be highly resistant to a broad range of metal(loid) species at toxic concentrations – notably 4.5 mM TeO32− determined by broth microdilution. Through screening of cell lysate in the presence of metal(loid) substrates, a mycothione reductase was characterized as a Te-specialized enzyme which reduces Te preferentially over Se. This is a surprising finding on the basis of reduction potentials for the two substrates. The standard reduction of potential for the reaction TeO32− + 3 H2O + 4e− ← → Te + 6 OH− is −0.57 V vs Hydrogen. The corresponding reduction of SeO32− is −0.366 V. Thus, SeO32− is the preferred substrate for reduction in the absence of a mechanism for substrate selectivity. We hypothesize that the R. erythropolis mycothione reductase may form the basis of a cloneable tellurium nanoparticle (cTeNP). In the third chapter, metal(loid) reductase substrate specificity is developed through directed evolution of a glutathione reductase-like metalloid reductase (GRLMR). The native substrate of GRLMR is selenodiglutathione (GS-Se-SG), where zerovalent selenium nanoparticles are formed in the presence of NADPH. Error prone polymerase chain reaction was used to create a library of ~100,000 GRLMR variants. The library was expressed in Escherichia coli with 50 mM SeO32− to select a GRLMR variant with 2 mutations. One mutation (a D to E) appears to be silent, whereas the other (L to H) resides within 5Å of the active site. Compared to the GRLMR parent enzyme, the evolved enzyme became less capable of reducing reduced glutathione (GSSG) and GS-Se-SG in favor of SeO32−. The evolved enzyme also gained an ability to reduce SeO42−. We have described this enzyme as a selenium reductase (SeR). This is the first known instance of the substrate specificity profile of a metal(loid) reductase changing as a result of directed evolution. In the fourth chapter, the cNP concept is discussed in greater detail. The cNP synthesis paradigm is loosely defined as a system of ligands, reductants, and inorganic cations – where ligands are peptides, reductants are enzyme-cofactor pairs, and inorganic cations are dietary or supplemented metal(loid) ions. This modular platform is adaptable to a wide variety of metal(loid)/enzyme/peptide systems. The story of the creation of a cloneable Se nanoparticle (cSeNP) is also retraced. Briefly, a bacterial endophyte Pseudomonas moraviensis subsp. Stanleyae was found to be capable of efficient selenium reduction under aerobic conditions. Continued characterization led to the discovery of GRLMR which unraveled the cellular mechanism for reducing SeO32−. The enzyme can endow host cells with selenium resistance through nanoparticle formation when cloned. GRLMR was further modified through the fusion of a selenium nanoparticle-binding peptide which improved overall kinetic rates, nanoparticle retention, and nanoparticle uniformity. In the fifth chapter, preliminary work is described which may enable further development of the next generation of cNPs through reduced enzyme mass/mericity and 'multicolored' nanoparticles. Work is described which investigates the plasticity of GRLMR towards reducing other metals such as bismuth. Fluorescence assisted cell sorting (FACS) was used to determine if the relative quantity of intracellular metal(loid) nanoparticles can be differentiated, which is hypothesized to correlate to relative metal(loid) reductase activity. Whereas selenium content could be discerned between active and inactive GRLMR-expressing bacteria, relative bismuth content has yet to be analogously discerned. On the other hand, work was done towards rationally designing a monomeric GRLMR; there are ongoing efforts to use machine learning to graft the active site of GRLMR into a different monomeric template. Finally, a Muchor racemosus cytochrome b5 reductase (Cb5R) was identified in the literature which may serve as an ideal candidate to develop more minimalistic cSeNPs. Initial work has revealed that the enzyme is particularly resistant to soluble expression, which may hinder its ability to function as a clonable contrast agent. However, ongoing work is being done to 'supercharge' the enzyme to enable more facile expression.